A Liquid‐Liquid‐Solid System to Manipulate the Cascade Reaction for Highly Selective Electrosynthesis of Aldehyde. (14th December 2022) - Huang, Hongling; Song, Xuedan; Yu, Chang; Wei, Qianbing; Ni, Lin; Han, Xiaotong; Huang, Huawei; Han, Yingnan; Qiu, Jieshan
Abstract: Electrocatalytic synthesis of aldehydes from alcohols exhibits unique superiorities as a promising technology, in which cascade reactions are involved. However, the cascade reactions are severely limited by the low selectivity resulting from the peroxidation of aldehydes in a traditional liquid‐solid system. Herein, we report a novel liquid‐liquid‐solid system to regulate the selectivity of benzyl alcohol electrooxidation. The selectivity of benzaldehyde increases 200‐fold from 0.4 % to 80.4 % compared with the liquid‐solid system at a high current density of 136 mA cm −2, which is the highest one up to date. In the tri‐phase system, the benzaldehyde peroxidation is suppressed efficiently, with the conversion of benzaldehyde being decreased from 87.6 % to 3.8 %. The as‐produced benzaldehyde can be in situ extracted to toluene phase and separated from the electrolyte to get purified benzaldehyde. This strategy provides an efficient way to efficiently enhance the selectivity of electrocatalytic cascade reactions. Abstract : A novel liquid‐liquid‐solid system was designed to manipulate the selectivity of cascade reaction and the selectivity for benzaldehyde is increased 200‐fold compared with the traditional liquid‐solid system. The produced benzaldehyde could be in situ extracted into the organic phase and separated from the complex electrolyte to achieve purification.